Faktor-faktor yang Memengaruhi Minat Generasi Muda terhadap Sektor Pertanian: Literature Review - Sitanggang, Andreas; Alfi, Hendra; Syafri, Edi (Universitas Galuh, 2025)
Human resources in the agricultural sector are faced with the problem of an aging workforce not accompanied by workforce regeneration. This problem is caused by the low interest of the younger generation to participate in the agricultural sector where various factors influence this interest. This study aims to provide an overview of the factors that influence the interest of the younger generation in the agricultural sector. This study was conducted using a descriptive approach with secondary data obtained from research articles related to the interest of the younger generation in the agricultural sector, as well as other supporting data. The data analysis used in this study is interactive analysis and bibliometric analysis. The results of the study show that the interest of the younger generation (<25 years) in the agricultural sector has been very low for the past few years (<10%), with the largest level of education of the workforce in the agricultural sector dominated by low education (>60%). The results of the bibliometric analysis of 34 articles related to the interest of the younger generation in the agricultural sector showed 11 influencing factors. The eleven factors are grouped into 2 clusters, namely cluster A consisting of 7 factors (age, education, experience, gender, income, land area, and parents), while cluster B consists of 4 factors (external factors, motivation, perception, and technology). There are three very dominant factors that influence the interest of the younger generation in the agricultural sector, namely income, education, and age.